Characteristics of East Sumatran Malay Dance as a New Dance Creation Engineering Foundation - Dilinar Adlin; Ruth Hertami; Aqsa Mulya (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
Malay Dance is one of the local content dances from North Sumatra Province - Indonesia. It is important that Malay dance is well understood by various groups, both students and the general public as art connoisseurs. Understanding of Malay dance aims to increase insight and comprehensive knowledge related to Malay dance and its characteristics. Thus, through a deep understanding of the characteristics of Malay dance, the skills to create new dances become more creative. This study aims to formulate or formulate the characteristics of Malay Dance as the foundation for engineering new dance creations. The results showed that the characteristics of Malay dance were grouped intointo three major parts, namely: a) head movement group which includes four (4) kinds of motion; b) group of hand movements which includes fourteen (14) kinds of motion; and c) group of footwork which is divided into eleven (11) kinds of motion. All of these characteristics become the foundation for engineering the creation of a new Malay dance by using the elements of energy, space, and time as a foothold.